Kierkegaard in seinem Verhältnis zur deutschen Romantik. Einfluss und Übervindung - Paulsen, Anna (KIERKEGAARDIANA, 1959)
Kierkegaard in seinem Verhältnis zur deutschen Romantik. Einfluss und Übervindung